Effects of tocotrienol on aging skin: A systematic review - Ghazali, Nur Izyani; Mohd Rais, Rahimah Zahidah; Makpol, Suzana; Chin, Kok Yong; Yap, Wei Ney; Goon, Jo Aan (Frontiers in Pharmacology, 2022)
The skin is the largest organ of the body that protects from mechanical, thermal, and physical injury. However, the function and appearance of skin visibly degenerates with age due to its frequent exposure to harmful effects of the environment, including ultraviolet irradiation and hazardous substances, in addition to the progression of oxidative stress in aging. These factors result in phenotypic changes in the skin, including wrinkling, pigmentation, reduced elasticity, and hydration during aging. Many natural antioxidant compounds have been studied extensively to reverse the signs of aging skin. Tocotrienols are a subfamily of vitamin E with potent antioxidant activity. Therefore, supplementation with vitamin E in the form of tocotrienol may efficiently protect skin from aging. In this review, the effects of tocotrienol on skin health, including pigmentation, moisture, and wrinkles during aging and UV exposure, were systematically evaluated based on a literature search of the PubMed and Scopus databases. The present data showed that tocotrienols protect the skin from inflammation, UV radiation and melanin accumulation. As the therapeutic value of tocotrienols grows, the potential of these vitamin E analogs to the skin requires further investigation.